Planning for the integration of refugee and host communities in Turkana County, Kenya - Terada, Y; Evans, D; Mwaniki, D (Refugee Studies Centre, University of Oxford, 2017)
The Kalobeyei New Settlement focuses on the creation of a spatial plan to guide settlement in both the short and the long term to the benefit of both host community and refugees.